Media Representations of Gendered Minority Practices: The Case of Polygamy in Israel - Sophia Abela Kiwanuka; Asia Parker; Lihi Ben Shitrit (Religions, 2023)
This paper critically examines how the mainstream media in Israel frame the phenomenon of polygamy among the minority Palestinian Bedouin community within the country. We identify four prominent media frames: (1) an “orientalist” frame, which considers Muslim women as in need of saving from their own culture and religion’s oppression by a modernizing state; (2) a “securitization” frame, which links the practice of polygamy to threats to the state’s security and to “Islamic terrorism;” (3) an “existential threat” frame, which reflects the Israeli Jewish majority’s anxieties about a demographic battle between Jews and Muslims in the country; and finally, (4) a “women’s rights” frame, which is the least prevalent, that addresses polygamy from the perspective of women’s equality and equal citizenship, and which is critical of the discriminatory policies of the state. Theoretically, the paper explicates how the media utilizes minority gendered practices to amplify Islamophobic sentiments in relation to a Muslim community, and how alternative framing and the featuring of critical Muslim women’s voices in the media might mitigate such harmful effects.